A Comment on Zoning, Returns to Scale, and the Value of Undeveloped Land - Colwell, Peter F.; Sirmans, C. F. (The Review of Economics and Statistics, 1993)
This paper revisits the relationship between land value and parcel size. The authors demonstrate that, using a simple arbitrage equilibrium argument, the value-size relationship is convex (concave) whenever land assembly (subdivision) is possible. They also explore further the impact of zoning on market outcomes. Copyright 1993 by MIT Press.